Prophylactic heme arginate therapy in acute intermittent hepatic porphyria – a case report - Krnetić, Žarko; Pešić, Tatjana; Savić, Željka; Jocić, Tatiana; Latinović Bošnjak, Olgica; Vračarić, Vladimir; Damjanov, Dimitrije (Vojnosanitetski pregled, 2022)
Introduction. Among the acute hepatic porphyrias, a small percentage of patients, predominantly female, present with recurrent cyclic attacks of acute intermittent porphyria that occur more than three times a year and sometimes at intervals of less than a month. In women, the attacks are typically related to the menstrual cycle, requiring several days of hospitalization and administration of heme arginate. For these patients, prophylactic heme arginate therapy may be the optimal treatment modality.  Case report. We presented a 40-year-old female patient who has been suffering from porphyria for seventeen years. The first attack occurred in 2003, presenting with severe neurological symptoms, requiring the use of heme arginate (Normosang®, Orphan Europe), which resulted in a favorable therapeutic response. In 2004 and 2007, gonadorelin analogue goserelin (Zoladex®) was used, but without beneficial effects on the course of the disease. In 2008, a preventive administration of heme arginate was initiated. The patient received heme arginate in the early phase of symptoms, every month in the premenstrual phase of the cycle, which resulted in milder symptoms, full recovery within 24 hours, lower doses of Normosang® (1-2 ampoules), and fewer hospital days (1-2 days) per month. This regimen has significantly improved the patient's quality of life and reduced the risk of potential adverse effects. Conclusion. Preventive use of Normosang® is the optimal therapeutic modality in patients with frequent, recurrent severe attacks that are unresponsive to other therapeutic regimens. As a result, patients have a better quality of life due to an effective, short-term, targeted treatment regimen.
Keywords: hem arginate; porphyrias; tertiary prevention; treatment outcome